Association between salt sensitivity and target organ damage in essential hypertension - (:unkn) unknown (My University, 2000)
Cardiovascular events occur more frequently in sodium-sensitive patients with essential hypertension; recently, sodium sensitivity was shown to be a cardiovascular risk factor independently of other classic factors such as blood pressure and cigarette smoking This study examined the relationship between salt sensitivity status and target organ damage in hypertensive patients. Ninety-six patients (35 men, 61 women) with moderate essential hypertension were studied for salt sensitivity status and the presence of target organ damage, including hypertensive retinopathy, serum creatinine, creatinine clearance, and urinary albumin excretion (UAE). Four different patterns of left ventricular anatomic adaptation were identified by categorizing patients according to the values of left ventricular mass index and relative wall thickness by the means of echocardiography. Forty-five (47%) patients were shown to be salt-sensitive, in contrast to 51 (53%) salt-resistant subjects. Serum creatinine and UAE were significantly higher in the group of salt-sensitive hypertensives (P < .05 and P < .001, respectively). Left ventricular mass index (LVMI), relative wall thickness (RWT), and left atrial index (LAI) were all significantly higher in the group of salt-sensitive hypertensive patients. Concentric hypertrophy was significantly more prevalent in the salt-sensitive group (37.8% v 11.8%; P < .01). The prevalence of hypertensive retinopathy in the salt-sensitive group was 84.4%, in contrast to 59.6% in the salt-resistant group (P < .01). Multivariate regression analysis revealed salt sensitivity as a significant predictor of LVMI, RWT, and UAE, independently of age, body mass index, and mean blood pressure. In conclusion, salt-sensitive hypertensive patients are more prone to develop severe hypertensive target organ damage that may enhance their risk of renal and cardiovascular morbidity.
Keywords: Adult; Female; Humans; Middle Aged; Prevalence; Male; Blood Pressure; Hypertension; Heart Diseases; Retinal Diseases; Sodium Chloride, Dietary